2019
DOI: 10.21157/j.ked.hewan.v13i1.5832
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Newcastle Disease Virus Circulates in some districts in Aceh

Abstract: The objectives of this study were to assess the diversity of Newcastle Disease Virus (NDV) isolates; to detect and isolate NDV from poultry; and to identify and characterize NDV by serological and molecular assays. A total of 84 cloacal-oropharynx isolates of poultry was collected from privately owned poultries and poultry markets from 12 districts in Aceh Besar and Banda Aceh. Screening was performed by real time reverse transcriptation-polymerase chain reaction (rRT-PCR) to 15 isolates of poultry. Selected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“… Kencana et al (2012) reported that 10 domestic chicken samples collected from field cases in 2008–2009 in Bali, Indonesia, were positive to be infected by the acute NDV. NDV infection in domestic chicken, broiler chicken, and waterfowl in Aceh, Indonesia, is dominated by virulent strains ( Darniati et al , 2015 ; Daud et al , 2019 ). In addition, several pathogenic isolates have been isolated from reared ducks ( Liu et al , 2010 ; Zhang et al , 2011; Panus et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… Kencana et al (2012) reported that 10 domestic chicken samples collected from field cases in 2008–2009 in Bali, Indonesia, were positive to be infected by the acute NDV. NDV infection in domestic chicken, broiler chicken, and waterfowl in Aceh, Indonesia, is dominated by virulent strains ( Darniati et al , 2015 ; Daud et al , 2019 ). In addition, several pathogenic isolates have been isolated from reared ducks ( Liu et al , 2010 ; Zhang et al , 2011; Panus et al , 2015 ).…”
Section: Introductionmentioning
confidence: 99%